From deficiency to sufficiency : ensuring food security policy in Ciamis Regency, Indonesia - Suwarlan, Erlan; Budiawan, Arie; Suparman, Agus Nurulsyam; Taufik, Otong Husni; Dewi, Maya Puspita (Department of Government Studies Universitas Muhammadiyah Makassar, 2025)
Several issues contribute to food deficiency, such as failure to maintain local government food reserves, low food diversification, declining fertility of agricultural land, and damaged agricultural infrastructure. The purpose of this study is to find out how local governments collaborate to ensure food sufficiency in Ciamis Regency. Using an explanatory research method, where data collection is done through interviews and observations, and data is processed through the stages of reduction, data presentation, and conclusion/verification. The research findings found that the initial conditions; the activities of the Ciamis District Food Security Council show the involvement of various actors. The Food Security Agency, as the lead sector, is responsible for coordinating food security efforts at the local level, as evidenced by coordination meetings. The institutional design executed by the Food Security Council provides coordination for all stakeholders involved in food security efforts. Collaborative processes are implemented through dialog forum involving representatives from different levels of government, including district, provincial and national levels. The Collaborative Governance approach to achieving food security in Ciamis Regency highlights the important role of institutions and leadership in enabling this process, as well as the importance of coordination and cooperation among multiple stakeholders.